Pulmonary artery catheter induced pulmonary haemorrhage - Shammaa, M Louai (BMJ Publishing Group, 2009)
Since its introduction three decades ago, the pulmonary artery (PA) catheter has brought insights into pathophysiology of many diseases enabling intensivists to treat critical conditions much more precisely and securely. PA indications are widening, and those working in an intensive care environment feel more secure in handling critical conditions with objective data. However, PA-induced pulmonary haemorrhage is a well-recognised, uncommon, yet potentially lethal, complication of PA catheter. We report a case with PA haemorrhage induced by placement of the PA catheter during coronary artery bypass surgery. A contrast-enhanced CT scan of the chest confirmed spontaneous remission of the haemorrhage after 7 weeks of the injury without the need for any intervention.